Simultaneous transmission/absorption photometry of particle-laden filters from wildland fires during the Biomass Burning Observation Project (BBOP) field campaign. (December 2020) - Presser, Cary; Nazarian, Ashot; Chand, Duli; Conny, Joseph M.; Sedlacek, Arthur; Hubbe, John M.
Abstract: Transmissivity and absorptivity measurements were carried out simultaneously in the visible (wavelength of 532 nm) at laboratory conditions using particle-laden filters obtained from a three-wavelength particle/soot absorption photometer (PSAP). The particles were collected on filters from wildland fires over the Pacific Northwest during the Department of Energy Biomass Burning Observation Project (BBOP) field campaign in 2013. The objective of this investigation was to apply this measurement approach, referred to as simultaneous transmission/absorption photometry (STAP), to estimate the aerosol extinction coefficient from actual field-campaign filter aerosol, and compare results with the PSAP. The STAP approach offers several advantages over the PSAP, including estimation of the extinction coefficient from temperature measurements (avoiding the complexities associated with filter reflectivity/scattering measurements), as well as determination of the filter optical properties and filter effects on particle absorption (resulting in particle absorption enhancement). The experimental arrangement included a laser probe beam impinging normal to the particle-coated surface of a vertically mounted filter, and a thermocouple placed flush in the middle of (and in thermal contact with) the filter uncoated back surface. With this simple arrangement, the transmissivity and absorptivity were determined simultaneously at a given laser beam wavelength. The measurement repeatability was better than 0.3 K (95% confidence level) for temperature and 0.4 mW for laser power. The limit of detection for the extinction coefficient was estimated to be (8–12) Mm −1 (95% confidence level) at about 1.9 mW laser power. The extinction coefficient was determined through measurement of both PSAP blank and exposed filters. Filters were obtained from nine different aircraft flights conducted during the BBOP campaign, representing different flight patterns, days, stages of burning, landscapes, and wildland fires. The STAP extinction coefficient matched the darkness of the filter coating, however the PSAP-filter results did not follow the same order. Although there were differences in transmissivity between the two techniques, the estimated values for absorption coefficient were in good agreement. Highlights: Extinction coefficient results from a novel measurement technique: simultaneous transmission/absorption photometry (STAP). Comparison of STAP results to particle/soot absorption photometry (PSAP). Evaluation of PSAP filters from the Biomass Burning Observation Project (BBOP) field campaign. Variety of particles observed from the BBOP PSAP filters.